Virulence and molecular diversity within Colletotrichum lindemuthianum isolates from Andean and Mesoamerican bean varieties and regions - Mahuku, George S.; Riascos, JJ (Springer, 2004)
Virulence on a standard set of 12 common bean differential varieties, DNA sequence of repetitive-elements (Rep-PCR) and random amplified microsatellites (RAMS) were used to assess the genetic variability of 200 Colletotrichum lindemuthianum isolates collected from Andean and Mesoamerican bean varieties and regions. High levels of pathotypic (90 pathotypes) and genetic diversity (0.97) were identified among 200 isolates, revealing that C. lindemuthianum is a highly diverse pathogen. Although a significant number of pathotypes were common to Andean and Mesoamerican regions, many more were only found in the Mesoamerican region. Cluster analysis of virulence and molecular data did not separate isolates into groups that were structured with common bean gene pools. No genetic differentiation (G ST=0.03) was apparent between Andean and Mesoamerican isolates of C. lindemuthianum. The diversity exhibited by C. lindemuthianum does not appear to cluster according to common bean gene pools, and the high diversity found in the Mesoamerican region seems to indicate that C. lindemuthianum originated and was disseminated from this region. Due to the high genetic variation exhibited by C. lindemuthianum, stacking major resistance genes appears to be the best option for developing cultivars with durable anthracnose resistance.